2011
DOI: 10.1155/2011/648324
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Multiwall Carbon Nanotubes/Polystyrene Composites Prepared via Coagulation Precipitation Technique

Abstract: Coagulation technique was applied for preparation of multiwall carbon nanotube- (MWNT-)containing polystyrene (PSt) composite materials with different MWNT loading (0.5–10 wt.%). Scanning and transmission electron microscopies were used for investigation of the morphology and structure of produced composites. It was shown that synthesis of MWNT/PSt composites using coagulation technique allows one to obtain high dispersion degree of MWNT in the polymer matrix. According to microscopy data, composite powder con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The preparation of the CF/MWNT composite in PP was performed by coagulation precipitation technique as follows. A calculated amount of milled CFs and MWNTs was placed into a PP solution in o ‐xylene with PP concentration 10 wt% with a filler concentration 100 g/l.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the CF/MWNT composite in PP was performed by coagulation precipitation technique as follows. A calculated amount of milled CFs and MWNTs was placed into a PP solution in o ‐xylene with PP concentration 10 wt% with a filler concentration 100 g/l.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling the adhesion of PMMA and PE matrices to the MWCNT surface using HyperChem 8.0 (molecular mechanics, MM þ force field) showed that adhesion of the PE matrix is 1.5-2 times higher as compared to the PMMA matrix. This provides a more uniform distribution of nanotubes, which is achieved in the case of the PE matrix [29] ( Figure 1H). The optical microscopy images show the initial nanotubes are mostly distributed uniformly within the PE matrix, without a significant number of aggregates, while the milled nanotubes show even a relatively greater number of the observed MWCNT aggregates.…”
Section: Structural Properties Of Mwcnt/polymer Compositesmentioning
confidence: 90%
“…Due to its low viscosity, the method tends to facilitate the dispersion of nanoparticles in the polymer matrix, which may or may not be associated with high energy sonication devices, and mechanical agitation to promote exfoliation/dispersion of nanoparticles and assist in achieving a state of homogeneous dispersion. This method has been very efficient in dispersing nanoparticles, but in general, large quantities of solvent compared to the mass of the nanocomposite obtained are required [4,5]. In addition, from the best of our knowledgement, there are a few works that had prepared nanocomposites using solution mixing techniques [6][7][8][9][10] with HDPE as a matrix, very probably due to time consumption of the method and the fact that organic solvents in general are employed.…”
Section: Introductionmentioning
confidence: 99%